Assessing Intestinal Health. In Vitro and Ex vivo Gut Barrier Models of Farm Animals: Benefits and Limitations - Ghiselli, Federico; Rossi, Barbara; Piva, Andrea; Grilli, Ester (Frontiers in Veterinary Science, 2021)
Animal performance is determined by the functionality and health of the gastrointestinal tract (GIT). Complex mechanisms and interactions are involved in the regulation of GIT functionality and health. The understanding of these relationships could be crucial for developing strategies to improve animal production yields. The concept of “gut health" is not well defined, but this concept has begun to play a very important role in the field of animal science. However, a clear definition of GIT health and the means by which to measure it are lacking. In vitro and ex vivo models can facilitate these studies, creating well-controlled and repeatable conditions to understand how to improve animal gut health. Over the years, several models have been developed and used to study the beneficial or pathogenic relationships between the GIT and the external environment. This review aims to describe the most commonly used animals’ in vitro or ex vivo models and techniques that are useful for better understanding the intestinal health of production animals, elucidating their benefits and limitations.